EVALUASI SISTEM PENGENDALIAN INTERNAL ATAS PERSEDIAAN BARANG DAGANG DALAM MENINGKATKAN EFEKTIVITAS & EFISIENSI PADA CV. SUKSES GLOBAL MANDIRI) - Reumiga Sabili Purnama; Indupurnahayu Indupurnahayu; Hurriyaturohman Hurriyaturohman (JURNAL PUNDI, 2023)
This study aims to assess the effectiveness & efficiency of the implementation of the internal control system in CV. Independent Global Success. This study uses descriptive qualitative methods in the form of documentation, observation and quantitative, namely to calculate the results of the questionnaire on the effectiveness & efficiency of internal control in accordance with the theory. From the research results, it can be seen that the company in implementing the internal control system for merchandise inventory has been running effectively and efficiently with a percentage of 80.06%. From these results indicate that there has been a separation between related functions. Monitoring of merchandise inventory is also carried out periodically through stock taking activities. However, there are still weaknesses, namely the absence of access restrictions between the entry and exit of the warehouse and the absence of CCTV placement in the goods storage area.Keywords: Internal Control System, Inventory, Effectiveness & Efficiency.